PENGARUH MODEL PEMBELAJARAN TIME TOKEN (TT) TERHADAP KETERAMPILAN BERBICARA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SDN JATIKALANG I - Agustin, Freeri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low skill of students when asking questions and discussing when learning Indonesian takes place makes learning outcomes decrease. Teachers who are less creative in processing learning materials make students unmotivated and lazy to accept learning materials. Teachers who tend to be selective with active students only make students who are less active are reluctant to have an opinion and choose to listen to the opinions of active students without commenting. Students who are less active in speaking during the discussion are ignored by the teacher. The teacher only assumes that the opinions of active students are always right. The purpose of this study is to provide speaking skills of students who are less active through the Time Token learning model in Indonesian class V subjects at SDN Jatikalang I. This type of research uses classroom action research using two research cycles. The research emphasizes the results of speaking skills and the implementation of student learning when speaking in conveying ideas before the research is carried out and after the research is carried out. The research sample includes fifth grade students consisting of 20 students. The data collection techniques used are observation (observation), conducting interviews with sources, and collecting image evidence (documentation). At the pre- cycle stage the speaking skill score was still below the average of 50.06 (good enough). In the first cycle, the speaking skill score rose to 79.64 (good). The second cycle stage experienced a significant progress of 94.34 (very good). The value of the implementation of student learning in the pre-cycle stage is 2,75 (not good). The value of the implementation of the first cycle of learning is 3,75 (good enough). The value of the implementation of learning second cycle is 4,75 (good). The conclusion that can be drawn is that the Time Token learning model is very influential on students' speaking skills in Indonesian class V subjects at SDN Jatikalang I.